2013
DOI: 10.1007/s13659-013-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Induced biosyntheses of a novel butyrophenone and two aromatic polyketides in the plant pathogen Stagonospora nodorum

Abstract: Fungal aromatic compounds comprise an important and structurally diverse group of secondary metabolites. Several genome sequencing projects revealed many putative biosynthetic gene clusters of fungal aromatic compounds, but many of these genes seem to be silent under typical laboratory culture conditions. To gain access to this untapped reservoir of natural products, we utilized chemical epigenetic modifiers to induce the expression of dormant biosynthetic genes. As a result, the concomitant supplementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Given that secondary metabolites have been shown to be involved in fungal pathogenesis (Mobius and Hertweck, ; Collemare and Lebrun, ), it is reasonable to postulate that some of the secondary metabolites encoded by the 38 biosynthetic gene clusters in P. nodorum could play important roles in its interactions with the host. Despite previous efforts to uncover the phytotoxins and other secondary metabolites from P. nodorum (Devys et al ., 1978; 1980; 1982, 1992; Tan et al ., ; Yang et al ., ), this is the first report of a perylenequinone isolated from this important wheat pathogen. Nevertheless, elsinochromes have been isolated from related Stagonospora and Phaeosphaeria fungi (Nicolet and Tabacchi, ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that secondary metabolites have been shown to be involved in fungal pathogenesis (Mobius and Hertweck, ; Collemare and Lebrun, ), it is reasonable to postulate that some of the secondary metabolites encoded by the 38 biosynthetic gene clusters in P. nodorum could play important roles in its interactions with the host. Despite previous efforts to uncover the phytotoxins and other secondary metabolites from P. nodorum (Devys et al ., 1978; 1980; 1982, 1992; Tan et al ., ; Yang et al ., ), this is the first report of a perylenequinone isolated from this important wheat pathogen. Nevertheless, elsinochromes have been isolated from related Stagonospora and Phaeosphaeria fungi (Nicolet and Tabacchi, ; Li et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The study found that the concentration of alternariol in the culture of an sch1 mutant strain is 200-fold greater than the wild-type P. nodorum , although the relationship between sch1 and alternariol biosynthesis is still unknown. Another new compound, (+)-4ʹ-methoxy-(2S)-methylbutyrophenone ( Figure 2 ), was isolated from P. nodorum recently by supplementing epigenetic modifiers to the culture medium (Yang et al 2013 ). These two most recent P. nodorum SM studies have highlighted that both genetic and epigenetic approaches can be used to induce the expression of otherwise silent SM pathways in laboratory culture conditions (Brakhage & Schroeckh 2011 ).…”
Section: Parastagonospora Nodorum Pathobiology and Secondarymentioning
confidence: 99%
“…So far, all characterized fungal PR-PKSs were shown to produce 6-methylsalicylic acid ( Figure 3 ). Since no 6-methylsalicylic acid has been isolated from P. nodorum and SNOG_00477 is the only PR-PKS in P. nodorum , this makes SNOG_00477 a promising candidate PKS gene for mellein production (Yang et al 2013 ). SNOG_14927 is another possible candidate PKS suggested by Yang et al ( 2013 ); it has the identical domain architecture as SNOG_00477 and 6-methylsalicylic acid PR-PKSs.…”
Section: Genomic Outlook For the Sm Biosynthetic Potential Of mentioning
confidence: 99%
“…So far, none of the products of these secondary metabolite gene clusters have been identified, and only a few secondary metabolites have been identified in this species (7). These metabolites include (R)-mellein and derivatives (8,9), septorines (10,11), mycophenolic acid (8), alternariol (12), and (ϩ)-4=-methoxy-(2S)-methylbutyrophenone (13).…”
mentioning
confidence: 99%